Validitas dan reliabilitas instrumen penilaian berbasis android untuk menilai kemampuan siswa SMK dalam mendesain busana secara digital - Fathia Rohmah; Ani Rusilowati; Supriyadi Supriyadi; Trisnani Widowati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The aims of this research and development are (1) to develop an android-based assessment instrument to assess the ability to design clothes digitally, (2) to test the validity and reliability of the instruments developed, (3) to test the practicality of using android-based assessment instruments. The research model uses the Borg & Gall model which consists of ten development steps, namely: (1) research and data collection (2) planning, (3) product draft development, (4) field trials, (5) initial product improvement, ( 6) field trials, (7) improvement of the results of field tests, (8) field implementation tests, (9) improvement of the final product, and (10) dissemination and implementation. The data analysis technique uses the Aikens'V formula to test content validity, Cronbach's Alpha to analyze reliability, and percentages to test practicality. The results of the study (1) obtained an assessment instrument in the form of a Likert scale, 4 options, equipped with a rubric for assessing fashion design products digitally. The instrument is constructed on 4 dimensions/aspects of 15 indicators. (2) the assessment instrument developed is valid with a Vcount of 0.93 and reliable with a reliability coefficient of 0.91. (3) The use of instruments in the good category with an average score of 87.5%.